The An electronic equipment-based nursing homes using “care dog” device - V. Sujatha,C. Rathiga, .K. Prasanna,.S. Maha Lakshmi,sujitha, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
This article highlights the innovative concept and practical benefit of converting an intelligent automobile into an electronic "nursing dog" for a nursing home. The system was pre-analyzed. Then we constructed a software platform based on ARM core STM32F103 single chip microcomputer control automated control system, comprising the primary programme of automatic control, sensor data processing, voluntary obstacle avoidance, and robotic arm grasping method. The system also uses three communication technologies: wireless WIFI, Bluetooth, and infrared. Finally, the system's stability and practicality were validated by collaborative debugging of the equipment's photovoltaic-assisted power production, autonomous driving, remote control, video transmission, and robotic arm intelligence. Grabbed and awaited relevant research.